Analisis Implementasi Pengendalian Internal terhadap Pengelolaan Kas Pada UMKM Teko Teh - Rista, Raharka Prismadifa; Azmiyanti, Rizdina (Jurnal Akuntansi dan Keuangan, 2025)
The purpose of this study was to determine the internal control of cash management at UMKM Teko Teh. This research method used is qualitative research with data collection techniques using interviews, observations, and documentation of primary and secondary data. The results showed that UMKM Teko Teh has had adequate management of cash receipts and disbursements, but there are still shortcomings because there is no separation of the sales function from cash receipts and there is no financial recording with good journaling. The internal controls applied are still general and quite consistent, it's just that there are risks from employee negligence and recording financial statements that are not in accordance with theory. The solution that can be applied is to develop a more optimal digitization method by adding the Qris payment method and be balanced with financial literacy by the owner.